Maintaining the Phenotype Stability of Chondrocytes Derived from MSCs by C-Type Natriuretic Peptide - Shi, Quan; Qian, Zhiyong; Liu, Donghua; Sun, Jie; Xu, Juan; Guo, Ximin (Frontiers in Physiology, 2017)
Mesenchymal stem cells (MSCs) play a critical role in cartilage tissue engineering. However, MSCs-derived chondrocytes or cartilage tissues are not stable and easily lose the cellular and cartilage phenotype during long-term culture in vitro or implantation in vivo. As a result, chondrocytes phenotypic instability can contribute to accelerated ossification. Thus, it is a big challenge to maintain their correct phenotype for engineering hyaline cartilage. As one member of the natriuretic peptide family, C-type natriuretic peptide (CNP) is found to correlate with the development of the cartilage, affect the chondrocytes proliferation and differentiation. Besides, based on its biological effects on protection of extracellular matrix of cartilage and inhibition of mineralization, we hypothesize that CNP may contribute to the stability of chondrocyte phenotype of MSCs-derived chondrocytes.